Penegakan Hukum Administrasi Dalam Sengketa Kepemilikan Rumah Toko - Matuankotta, Jacky Alko Lazarus; Nendissa, Renny Heronia; Holle, Erick Stenly (Faculty of Law, Universitas Pattimura, 2025)
Article 28D paragraph (1) of the 1945 Republic of Indonesia Constitution states that: